The effects of electronic cigarette aerosol exposure on inflammation and lung function in mice - Larcombe, Alexander; Janka, M.; Mullins, Ben; Berry, L.; Bredin, Arne; Franklin, P. (American Physiological Society, 2017)
Electronic cigarette usage is increasing worldwide, yet there is a paucity of information on the respiratory health effects of electronic cigarette aerosol exposure. This study aimed to assess whether exposure to electronic cigarette (e-cigarette) aerosol would alter lung function and pulmonary inflammation in mice and to compare the severity of any alterations with mice exposed to mainstream tobacco smoke. Female BALB/c mice were exposed for 8 wk to tobacco smoke, medical air (control), or one of four different types of e-cigarette aerosol. E-cigarette aerosols varied depending on nicotine content (0 or 12 mg/ml) and the main excipient (propylene glycol or glycerin). Twenty-four hours after the final exposure, we measured pulmonary inflammation, lung volume lung mechanics, and responsiveness to methacholine. Mice exposed to tobacco cigarette smoke had increased pulmonary inflammation and responsiveness to methacholine compared with air controls. Mice exposed to e-cigarette aerosol did not have increased inflammation but did display decrements in parenchymal lung function at both functional residual capacity and high transrespiratory pressures. Mice exposed to glycerin-based e-cigarette aerosols were also hyperresponsive to methacholine regardless of the presence or absence of nicotine. This study shows, for the first time, that exposure to e-cigarette aerosol during adolescence and early adulthood is not harmless to the lungs and can result in significant impairments in lung function.